THE ROLE OF THE COASTAL STATES TO THE PROTECTION OF MARINE ENVIRONMENT IN JOINT DEVELOPMENT AGREEMENT - Wartini, Sri (Indonesian Journal of International Law, 2017)
Maritime boundary disputes with neighboring states, especially in continental shelf driven by potentially large hydrocarbon deposits lying in overlapping continental shelf. Presently, there are many states remain in the hydrocarbon extraction and exploration in the form of joint development Agreement. The impacts of the joint development in conducting exploitation in the offshore which become the disputing continental shelf may potentially cause pollution or environmental damage in the adjacent area. The objective of the research is to evaluate whether the joint development Agreement in disputing continental shelfconcerns to the protection of the marine environment.The paper undertakes a critical examination of the issues relating to the role of coastal states to protect the marine environment in Joint Development Agreement.The paper is a normative research and the methodology employed in this paper is library research. While the approaches employed in the research are statutory approach, comparative approach and conceptual approach. The research finds that the protection of the marine environment in joint development agreement in the joint development zone needs has not carried out optimumly particularly in developing countries.